1999
DOI: 10.1046/j.1523-1747.1999.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Gli1 Protein is Expressed in Basal Cell Carcinomas, Outer Root Sheath Keratinocytes and a Subpopulation of Mesenchymal Cells in Normal Human Skin

Abstract: Genetic studies of patients with the nevoid basal cell carcinoma syndrome have led to the recognition of the importance of the hedgehog signaling pathway in the development of basal cell carcinomas of the skin. Although hedgehog signaling is known to be important in hair follicle development, the function of this pathway in adult skin and the mechanism by which activation of this pathway leads to basal cell carcinoma development remain to be established. The Gli1 family of transcription factors mediates hedgeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 12 publications
8
59
0
3
Order By: Relevance
“…We observed weak cytoplasmic immunostaining with antibodies against GLI1 in the outer root sheath of the hair follicle and in the IFE, consistent with a previous study (43). In contrast, strong staining with the anti-GLI1 antibody was seen in the nuclei of progenitor cells in the sebaceous gland (Fig.…”
Section: Ihh and Gli1 Expression In Normal Epidermissupporting
confidence: 91%
“…We observed weak cytoplasmic immunostaining with antibodies against GLI1 in the outer root sheath of the hair follicle and in the IFE, consistent with a previous study (43). In contrast, strong staining with the anti-GLI1 antibody was seen in the nuclei of progenitor cells in the sebaceous gland (Fig.…”
Section: Ihh and Gli1 Expression In Normal Epidermissupporting
confidence: 91%
“…Overexpression of GLI1 in the epidermis of transgenic animal models produces BCC-like lesions (21,22) and will transform rodent epithelial cells in cooperation with adenovirus EIA (23), indicating that unregulated expression of GLI1 is oncogenic. Recent studies have shown that GLI1 expression is greatly increased in BCCs but not in the surrounding normal tissue, consistent with a central role in tumor formation (21,24,25).…”
mentioning
confidence: 80%
“…Having shown that expression of GLI1 and GLI2act in cultured keratinocytes leads to an increase in JUN mRNA and protein, we investigated JUN expression in BCC, which shows strong expression of HH pathway components PTCH, GLI1 and GLI2 (Hahn et al, 1996;Johnson et al, 1996;Ghali et al, 1999;Regl et al, 2002). We measured the mRNA levels of JUN, GLI1, GLI2 and PTCH by qRT-PCR in samples of human BCC (n ¼ 6) and normal human skin (n ¼ 3) (Figure 2a).…”
Section: Jun Expression Is Increased In Response To Gli In Human Keramentioning
confidence: 99%